2021
DOI: 10.3390/nu13020641
|View full text |Cite
|
Sign up to set email alerts
|

Low Dietary Variety and Diabetes Mellitus Are Associated with Frailty among Community-Dwelling Older Japanese Adults: A Cross-Sectional Study

Abstract: The association between dietary diversity and frailty remains unknown in older people. We evaluated whether a limited dietary variety is associated with frailty in older adults with diabetes mellitus (DM). This cross-sectional investigation included 1357 adults (median age: 77 years, women: 61.3%). DM was determined by self-reporting, the Dietary Variety Score (DVS) was used to evaluate dietary variety, and the revised Japanese version of the Cardiovascular Health Study criteria evaluated frailty. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Some studies, including our previous studies, revealed a relationship between dietary habits and frailty status. For example, low dietary variety or a low number of food categories was an independent risk factor for frailty, 12 and higher protein intake was associated with a reduced risk for frailty in older women. 13 Taking these findings together, dietary variety rather than the number of daily meals might be more strongly related to frailty status.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, including our previous studies, revealed a relationship between dietary habits and frailty status. For example, low dietary variety or a low number of food categories was an independent risk factor for frailty, 12 and higher protein intake was associated with a reduced risk for frailty in older women. 13 Taking these findings together, dietary variety rather than the number of daily meals might be more strongly related to frailty status.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it was possible that dietary habits affected blood indicators. Hayakawa et al [ 21 ] reported that blood components, such as serum creatinine and HbA1c, were significantly different among the dietary variety score groups. In fact, the results of our study also revealed that after multiple logistic regression analyses, the total cholesterol and HDL cholesterol levels were not identified as significant variables for lower cognitive function ( Table 4 ), and this corresponds to the results from another previous study by Dalmeijer et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary variety score was calculated using the intake frequencies of 9 food categories (fish, meat, eggs, soy products, potatoes, fruit, seaweed, green and yellow vegetables, and fats and oils; in the original paper, 10 items were calculated, including milk, but in this study, milk was considered to be in the same family as cheese, so it was excluded). For each participant, a score of 1 was given for each food category if it was eaten every day, and a score of 0 was given if it was eaten once every 2 days, once or twice a week, or not at all; the total score (0 to 9) was then calculated [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dietary variety score was calculated from the intake frequencies of 9 food categories (fish, meat, egg, soy products, potatoes, fruit, seaweed, green and yellow vegetables, and fats and oils: In the original paper, 10 items were calculated, including milk, but in this study, milk is a food of the same family as cheese, so it was calculated with 9 items excluding milk). A score of 1 was given for eating a food category every day; a score of 0 for eating once every 2 days, eating once or twice a week or not eating at all; and the total score (score 0 to 9) was calculated [20].…”
Section: Outcome Measuresmentioning
confidence: 99%